Achieving Sustainable Development in Business: The Implementation of Environmental Management Practices by Small and Medium Enterprises - MUHAMAD, AINA SYUHAILA; MAT, NIK HAZIMAH NIK; ZULKIFFLI, SITI NUR ‘ATIKAH (The journal of contemporary issues in business and government, 2021)
Over the past two decades, the issue of sustainability has received mixed opinions from people, especially in business world. The concept of Sustainable Development has slowly changing the view of modernisation and growth for worldwide development activities. Small and Medium-sized Enterprises (SMEs) tend to be opposed to the idea. The purpose of this study is to evaluate the implementation of Environmental Management Practices (EMP) among SMEs in Malaysia. Using the Data Envelopment Analysis (DEA) model, this study employed barriers and motivations as an input, while sustainable development elements are taken as an output. Findings show that the implementation level of EMP varied among companies, which consequently influences their level of sustainable development. The implications of the finding are discussed based on the concept of Goal-Setting Theory to explain the nexus between the company’s ability to set the right environmental goals and employees’ understanding of the signals sent to support the company’s sustainable development.